(untitled) (African Journal of Biomedical Research, 2020)
Breastfeeding knowledge of the mothers and support given to them by health care providers after delivery can influence mothers’ attitude to breastfeeding and their willingness to initiate breastfeeding early. The study assessed breastfeeding knowledge and factors associated with breastfeeding initiation among postpartum mothers in urban and rural areas of Ibadan. This cross-sectional study was conducted among three hundred and sixty (360) postpartum mothers who attended Primary and Private Health Centres in rural and urban areas of Ibadan, Oyo State, Nigeria. A semi-structured, interviewer-administered questionnaire was used to collect information on the socio-demographic characteristics, knowledge of breastfeeding, intention to breastfeed and factors which influence the breastfeeding initiation. Majority of the respondents were young adults within the age of 25-35 years, with mean age of 28.9±5.73years. Two third (71.4%) of them had good knowledge of breastfeeding and only 48.6% initiated breastfeeding early. A positive significant association was observed between breastfeeding knowledge and breastfeeding initiation (p<0.05). Complication during or before childbirth, mothers being educated by the health workers on breastfeeding initiation, help given to the mothers during initiation of breastfeeding by healthcare provider and rooming-in of mother and child were found to be significantly associated with breastfeeding initiation among the postpartum mothers (p<0.05). Adequate knowledge on the benefits of breastfeeding should be promoted among pregnant women during antenatal care and adequate supports should be given to postpartum mothers after delivery to enhance early breastfeeding initiation and practice of adequate breastfeeding.